Makna Dakwah Dalam Lirik Lagu Love and Life Karya Baraa Masoud - Al Adawiyah, Robiah; Sunaryanto (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2025)
This research aims to analyze the da’wah messages contained in the lyrics of Love and Life by Baraa Masoud using Charles Sanders Peirce's semiotic approach. This song was chosen because its lyrics are rich in Islamic values and effectively convey religious messages universally. This research employs a descriptive qualitative method with Charles Sanders Peirce's semiotic analysis as the analytical tool. This approach incorporates three main elements representamen, object, and interpretant to explore and interpret the symbolic meanings embedded in the song lyrics. Various types of qualitative research methods were considered to ensure the research objectives were clearly defined and effectively achieved. The findings reveal that the lyrics of Love and Life convey da’wah messages that include encouragement to love Allah, draw closer to Him, foster compassion for others, and practice values such as justice, patience, and gratitude in daily life. Moreover, the dakwah messages embedded in the lyrics encompass themes of faith (aqidah), religious practice (sharia), and morality (akhlaq).